Systematic phylogenetic analysis of influenza A virus reveals many novel mosaic genome segments. - Lam, T; Chong, Y; Shi, M; Hon, C; Li, J; Martin, D; Tang, J; Mok, C; Shih, SR; Yip, C; Jiang, J; Hui, R; et al. (2013)
Recombination plays an important role in shaping the genetic diversity of a number of DNA and RNA viruses. Although some recent studies have reported bioinformatic evidence of mosaic sequences in a variety of influenza A viruses, it remains controversial as to whether these represent bona fide natural recombination events or laboratory artifacts. Importantly, mosaic genome structures can create significant topological incongruence during phylogenetic analyses, which can mislead additional phylogeny-based molecular evolutionary analyses such as molecular clock dating, the detection of selection pressures and phylogeographic inference. As a result, there is a strong need for systematic screenings for mosaic structures within the influenza virus genome database. We used a combination of sequence-based and phylogeny-based methods to identify 388 mosaic influenza genomic segments, of which 332 are previously unreported and are significantly supported by phylogenetic methods. It is impossible, however, to ascertain whether these represent natural recombinants. To facilitate the future identification of recombinants, reference sets of non-recombinant sequences were selected for use in an automatic screening protocol for detecting mosaic sequences. Tests using real and simulated mosaic sequences indicate that our screening protocol is both sensitive (average >90%) and accurate (average >77%) enough to identify a range of different mosaic patterns. The relatively high prevalence of mosaic influenza virus sequences implies that efficient systematic screens, such as that proposed here, should be performed routinely to detect natural recombinant strains, potential laboratory artifacts, and sequencing contaminants either prior to sequences being deposited in GenBank or before they are used for phylogenetic analyses.